KANT ON JUSTICE - Seniye Tilev (Felsefe Dünyası)
In this paper I give a detailed account of Kant’s notion of justice in various respects. First, I discuss how Kant’s conception of the moral law – its form as a categorical imperative, as the synthetic a priori basis of moral reasoning, operates initially as a limiting condition for the moral agent not to violate freedom and rights of one another. In this connection I analyze Kant’s various formulations of categorical imperative and prioritize formula of universal law over its other formulations. Second, I argue that according to Kant justice and virtue make two sides of the same coin and principles of justice is the basis of all moral affairs (embracing not only external rights). Finally, I state that because moral purposiveness of reason demands realization of a system of justice, Kant sets constituting a civil condition and global justice as a duty towards which we all required to work as a moral duty.